Facile preparation of biodegradable dual stimuli-responsive micelles from waterborne polyurethane for efficient intracellular drug delivery. (13th November 2019) - Saeedi, Sara; Omrani, Ismail; Bafkary, Reza; Sadeh, Elaheh; Shendi, Hasan Kashef; Nabid, Mohammad Reza
Abstract : A novel waterborne polyurethane based on main chain degradation under acidic and reductive conditions of tumors was synthesized. Abstract : In spite of the easy synthesis of polyurethanes, some of them that are fully degradable in response to intracellular glutathione (GSH) and acid are less explored for targeted controlled drug delivery. Herein, novel glutathione and acid-degradable waterborne polyurethane (WPU) nanoparticles for redox and acid-triggered intracellular delivery of doxorubicin (DOX) as a model lipophilic anticancer drug are reported. The waterborne polyurethane nanoparticles are prepared from a polyaddition reaction of isophorone diisocyanate (IPDI) and a linear polyester polyol involving a disulfide linkage, followed by addition of an imine containing diol as a chain extender and dimethylolpropionic acid (DMPA) in the presence of dibutyltin dilaurate (DBTDL) as a catalyst. The resulting polyurethanes self-assemble into nanoparticles in water. Dynamic light scattering (DLS) and scanning electron microscopy (SEM) revealed fast swelling and disruption of nanoparticles under an intracellular reduction – acidic mimicking environment. In vitro release studies showed that in the presence of 10 mM GSH at pH 6.0, 74% of DOX was released from the DOX-loaded WPU nanoparticles in 24 h. MTT assay showed that the DOX-loaded WPU nanoparticles had a similar cytotoxicity for A375 human malignant melanoma cells to free DOX, and blank WPU nanoparticles had a low cytotoxicity to the cells. These results indicated that the GSH and acid-degradable WPU nanoparticles, as a novel, effective pH and redox-responsive nanocarrier, have potential for efficient intracellular drug delivery.